Impact of different pre-treatments and drying methods on quality and antioxidant properties of dried persimmon (Diospyros kaki L.) slices. (16th March 2020) - Khademi, Orang; Farrokhzad, Yusuf; Khangholi, Shahpour
This study was conducted to evaluate the effects of various pre-treatments and drying methods on the quality and antioxidant properties of persimmon slices. The persimmon fruits were harvested at maturity stage and divided into three groups: control without any pre-treatments, pre-treatment with 2% sucrose after slicing, and treatment with CO2 before slicing in order to remove astringency. Afterwards, all groups were subjected to three drying methods including sun drying (21 days), conventional oven drying (65°C for 24 hours) and vacuum oven drying (65°C for 18 hours). Then, the dried slices were assessed for antioxidants. Results indicated that persimmons subjected to astringency removal pre-treatments and sun dried had the best sensory quality. However, the pre-treatments reduced antioxidant properties as compared to other pre-treatments. Results also showed that sun dried samples had the best quality overall.